2006
DOI: 10.1007/s00122-006-0361-8
|View full text |Cite
|
Sign up to set email alerts
|

An updated ‘Essex’ by ‘Forrest’ linkage map and first composite interval map of QTL underlying six soybean traits

Abstract: DNA marker maps based on single populations are the basis for gene, loci and genomic analyses. Individual maps can be integrated to produce composite maps with higher marker densities if shared marker orders are consistent. However, estimates of marker order in composite maps must include sets of markers that were not polymorphic in multiple populations. Often some of the pooled markers were not codominant, or were not correctly scored. The soybean composite map was composed of data from five separate populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 64 publications
6
114
1
2
Order By: Relevance
“…However, at genomic regions where gaps between adjacent markers were greater than 10 cM in the map associations 0.005>P>0.0005 were accepted as a potentially significant association. Precedents (Hnetkovsky et al, 1996;Chang et al, 1997;Njiti et al, 1997;Kassem et al, 2006) have shown these criteria to be valid in later maps (Meksem et al, 2001a;Njiti et al, 2002;Yuan et al, 2002;Triwitaykorn et al, 2005;Ruben et al, 2006).…”
Section: Construction Of Qtl Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at genomic regions where gaps between adjacent markers were greater than 10 cM in the map associations 0.005>P>0.0005 were accepted as a potentially significant association. Precedents (Hnetkovsky et al, 1996;Chang et al, 1997;Njiti et al, 1997;Kassem et al, 2006) have shown these criteria to be valid in later maps (Meksem et al, 2001a;Njiti et al, 2002;Yuan et al, 2002;Triwitaykorn et al, 2005;Ruben et al, 2006).…”
Section: Construction Of Qtl Mapsmentioning
confidence: 99%
“…For example, Orf et al (1999a,b) identified QTL for seed yield in different linkage groups A2, B1, B2, D1a+Q, D1b+W, D2, F, J, L, and M of the soybean genome. Other authors identified QTL for yield on linkage groups C2, H, M (Specht et al, 1999), F (Reyna and Sneller 2001), J, L, M (Mansur et al, 1993(Mansur et al, , 1996, and N (Kassem et al, 2006) of the soybean genome. Three QTL for yield were found on linkage groups C1, I, and K using 136 SSR markers and a RIL population of Essex × Forrest (E × F) (Yuan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several QLT related to grain yield have been described in the scientific literature, maybe only a few of them have already been confirmed (Kassem et al 2006, Bernardo 2008, Sebastian et al 2010. QTL, which have already been selected in breeding programs and/or transferred to new cultivars are rare (Ainsworth et al 2012).…”
Section: Jis Rodrigues Et Almentioning
confidence: 99%
“…(Kassem et al, 2006) For instance, BSA was used for mapping of Fusarium wilt (FW) resistance with RAPD markers in the case of pigeonpea (Kotresh et al, 2006). On the other hand, in order to understand the complex nature of drought tolerance in chickpea, precise phenotypic data for 20 different root traits was analyzed using a QTL mapping approach.…”
Section: Comprehensive Genetic Maps Andmentioning
confidence: 99%